Development of Tolerance among Secondary School Students in Conditions of Russian Inclusive Education - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva; D. O. Romanov (Научный диалог)
The development of tolerance among secondary school students in the context of national inclusive education is considered. Special attention is paid to the creation of tolerant relations between classmates. The relevance of the chosen topic is determined by the implementation of the Federal law “On education in Russian Federation,” providing the use of inclusive techniques and technologies in learning and education. The ways of development of tolerance cited in six PhD of Education thesis are presented and analyzed. All works are dedicated to the development of general or ethno-cultural tolerance. It is shown that none of them examine the relation to adolescents with disabilities that is unexpected for the authors in the context of inclusive education. In addition, none of these dissertations pay attention to all classes within the concept of “basic school” (from 5th to 9th). It is noted that the majority of researchers propose to develop the tolerance of adolescents through problematic discussions. The authors focus on the position that the formation of tolerance foundations should happen in elementary school, and in 5-9 classes one has to deal with the development of this quality. The novelty lies in the idea, the essence of which is to supplement the educational standards for future teachers and educational psychologists by the new discipline “Acting skills in teaching practice.”